Digital Marketing: The Role of Digital Marketing For Micro, Small, And Medium Enterprises In Pematang Serai Village - Dewi Nurmasari Pane; Hikmatul Fadhilah Sianipar; Rahmadani (International Journal of Economics Accounting and Management, 2025)
This study aims to analyze the role of digital marketing in the development of Micro, Small, and Medium Enterprises (MSMEs) in Pematang Serai Village, Langkat Regency. By utilizing digital technologies such as social media and e-commerce platforms, MSMEs in this village strive to increase market reach, marketing efficiency, and the competitiveness of local products. The methodology used includes a qualitative approach through observation, interviews, and literature studies. The results show that the implementation of digital marketing has a positive impact on increasing sales and product recognition of MSMEs. Supporting factors for success include village government support, MSME enthusiasm, ongoing mentoring, and adequate digital infrastructure. However, challenges such as limited digital literacy and access to technology still need to be addressed. This study concludes that digital marketing has a strategic role in empowering MSMEs in rural areas and recommends improving training and digital infrastructure for sustainable MSME development